Reviewing The Role of Syi'ir on The Island of Java From Preaching to Economic Fulfillment - Bahruddin, Muhammad; Elyn Olima Verah; Khoironul Mubin; Siti Mahmudah; Umi Faridah (Jurnal Disastri (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2026)
This study offers a novel approach by integrating oral literature narratology and speech act theory in analyzing syi'ir as a form of social communication in Pesantren. Unlike previous studies that generally focus on the function of da'wah or the religious content of syi'ir, this study systematically maps the relationship between narrative structure, language strategies, and the pragmatic effects produced in the context of performance. The transformation of the function of syi'ir is understood not only at the thematic level, but also at the level of narrative mechanisms and communicative processes that shape the meaning and social orientation of the congregation. This research was conducted in Pesantren in East Java with sources from the pesantren community. The data consists of syi'ir and interviews conducted with the Islamic pesantren community. The theoretical contribution of this research lies in strengthening the integrative narratological-pragmatic analysis model as a framework for reading the dynamics of oral literature in a changing social context. This approach broadens the perspective of Javanese oral literature studies by placing text, performance, and communicative relations as a single, interrelated unit of analysis.